2022
DOI: 10.1021/acs.jpclett.2c03734
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the near 400 nm Absorption and Emission Band in the Synthesis of Cesium Lead Bromide Nanostructures: Metal Halide Molecular Clusters Rather Than Perovskite Magic-Sized Clusters

Abstract: In the synthesis of cesium lead bromide (CsPbBr 3 ) perovskite quantum dots, with an electronic absorption and emission band around 510 nm, and perovskite magic-sized clusters (PMSCs), with an electronic absorption and emission band around 430 nm, another distinct absorption and emission around 400 nm is often observed. While many would attribute this band to small perovskite particles, here we show strong evidence that this band is a result of the formation of lead bromide molecular clusters (PbBr 2 MCs) pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…There, LARP was utilized as is typical for the synthesis of perovskites, and showed that MHMCs can be formed in the absence of an A component both with and without an acidic passivating ligand, demonstrating an increased dependence on the amine ligand. However, like PMSCs, proportionally large quantities of passivating ligands are necessary as MHMCs have a large surface to volume ratio as a product of their small size and high degree of confinement [12,14,15]. Overall, the introduction of facile synthesis schemes such as LARP to produce stable, monodispersed nanocrystal populations has made the study of the varied size and morphological possibilities of PNCs more attainable.…”
Section: Synthesis Of Pqds Pmscs and Mhmcsmentioning
confidence: 99%
See 3 more Smart Citations
“…There, LARP was utilized as is typical for the synthesis of perovskites, and showed that MHMCs can be formed in the absence of an A component both with and without an acidic passivating ligand, demonstrating an increased dependence on the amine ligand. However, like PMSCs, proportionally large quantities of passivating ligands are necessary as MHMCs have a large surface to volume ratio as a product of their small size and high degree of confinement [12,14,15]. Overall, the introduction of facile synthesis schemes such as LARP to produce stable, monodispersed nanocrystal populations has made the study of the varied size and morphological possibilities of PNCs more attainable.…”
Section: Synthesis Of Pqds Pmscs and Mhmcsmentioning
confidence: 99%
“…Further investigation of this near 400 nm MHMC peak was undertaken to reconcile its observation in syntheses that contain the perovskite A component. A recent work by Win et al showed that in samples where there is an observed near 400 nm peak alongside PMSC and/or PQD peaks, this 400 nm peak should be attributed to MHMCs despite the presence of other, definitively perovskite, structures in the same solution [15]. Spectra from the 2023 Win et al study are shown in Figure 4, and show that in a synthesis which includes the perovskite A component ( a and c ), several peaks appear in the resultant absorbance and emission spectra.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligand-passivated PbBr 2 MCs exhibit first excitonic absorption and emission band peaked around 402 and 410 nm, respectively, which are bluer than both corresponding PQDs and perovskite magic-sized clusters (PMSCs). ,, Unlike their larger perovskite counterparts, the key difference among them is that metal halide MCs lack the A component that is present in PQDs and PMSCs with ABX 3 composition, as demonstrated by past work from our lab . Also, further study showed that metal halide MCs can be generated alongside PQDs and PMSCs even when the A component is present . More recent structural studies incorporating Raman, XRD, and TEM suggest that PbBr 2 -BTYA MCs consist of a possible layered structure where the layers are composed of tilted, corner-sharing [PbBr 6 ] 4– octahedra with a particle size of 2.0 ± 0.4 nm .…”
mentioning
confidence: 99%